Pendekatan Pelatihan On-Site dan Step by Step untuk Optimalisasi Fungsi Guru dalam Pembelajaran - Moch. Sholeh Y.A. Ichrom (Universitas Negeri Malang, 2016)
Remoteness of programme content from teachers' real work situation and unsuitability of approach employed were suspected as main reasons contributing to the failure of many inservise teacher training programmes. A step by step, onsite teacher training (SSOTT) model was tried out in this experiment to study if the weakness of inservise programmes could be rectified. As it was tried out in relation with kindergarten mathemathics it was then called SSOTT-MTW (Step by Step Onsite Teacher Training-Methemathics Their Way) model. Eighty four kindergartens were involved, in which 84 teachers and 877 pupils were recruited as experimental subjects. The teachers were devided into three group. One group was instructed by using One Period Teacher Training (OPOTT-MTW) model, second group was trained with SSOTT-MTW model and the last group was given no training (NTT) at all. Result of the experiment showed that the other groups. It was also shown that pupil and parents participation in teaching-learning activities also significantly improved.